Product Quality and Consumer Purchase Decisions in the Nigerian Soft Drink Industry - Omoniyi, Imouokhome Ebun; Osasere, Iyamu Gloria (NIU Journal of Management Sciences, 2026)
This study investigates the influence of product quality (aesthetics) on consumer purchase decisions, with specific reference to Coca-cola, a product of the Nigeria Bottling Company among undergraduate students at the University of Benin, Nigeria. The research adopts a quantitative design, utilized structured questionnaires to obtain data from 395 respondents. Product aesthetics, one of the attributes of product quality was theorized along three dimensions: product shape, product size, and product colour. Multiple regression analysis was employed to analyse the data and the hypothesis was tested at 0.05 significant level. Findings revealed that product quality (aesthetics) demonstrated a positive effect, affirming the role of packaging design in consumer appeal. The study concludes that product quality is a many-sided concept that significantly drives consumer purchase intentions and decisions. It was recommended that Nigerian soft drink industry should enhance redesign packaging to improve aesthetic appeal, and invest in durable packaging materials. Keywords: Product Aesthetics; Consumer Goods; Purchase Decision; Packaging Size; Packaging Colour; Packaging Shape.